Elastic modulus change and its relation with glass-forming ability and plasticity in bulk metallic glasses. (1st March 2019) - Yang, Ming; Liu, Xiongjun; Wu, Yuan; Wang, Hui; Wang, Jianbiao; Ruan, Haihui; Lu, Zhaoping
Abstract: In this work, we revealed the intrinsic relation between the modulus change upon heating and macroscopic properties such as glass-forming ability (GFA) and room-temperature plasticity in various metallic glasses. Specifically, GFA and plasticity can respectively be related to the softening rate right above the glass transition temperature ( T g ) and the degree of sub- T g relaxation. These relations can be understood in terms of the unified picture of potential energy barrier crossing. Above T g, the faster barrier crossing leads to the larger softening rate and the higher tendency of crystallization; below T g, the easier local rearrangement brings about the larger plasticity. Graphical abstract: